The Influence of Jordanian Electronic Journalism on Public Perception and Attitudes Towards Political Issues in Jordan - Safori, Amjad Omar (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aimed to examine the attitudes formed among the Jordanian public as a result of following political issues through Jordanian electronic newspapers and to assess the impact of this engagement on their perspectives. Methods: Using a descriptive research approach, this study employed a media audience survey methodology with an equal quota sample of 450 individuals representing the Jordanian public across three regions—North, Central, and South. Results: Findings showed that 90.4% of respondents follow political issues via Jordanian electronic newspapers, with the most closely followed topic being "political developments related to the Al-Aqsa Flood operation." The primary attitude formed was an "increase in political awareness among the public." Additionally, the influence of Jordanian electronic journalism in shaping respondents' priorities around political issues was moderate, particularly in "directing attention towards significant political topics." Conclusions: Jordanian electronic journalism plays an influential role in shaping public attitudes toward political matters and guiding their attention to these issues. A positive correlation was found between the frequency of following political issues in electronic newspapers and the cognitive, emotional, and behavioral effects experienced by respondents.